Panniculectomy and Cystectomy: An Approach to the Morbidly Obese Patient - Lee A. Hugar; Robert M. Turner; Jeffrey A. Gusenoff; Andres F. Correa; Bruce L. Jacobs; Benjamin J. Davies (Case Reports in Urology)
The obese patient undergoing radical cystectomy faces a unique set of challenges. We present the case of a 68-year-old gentleman who presented to our institution with Bacillus Calmette-Guerin refractory disease, a body mass index of 38.5, and a large pannus. The present paper describes our technique for performing radical cystectomy with ileal conduit urinary diversion and concomitant panniculectomy. We discuss the impact of obesity on patients undergoing radical cystectomy and how this may be mitigated by panniculectomy.